(untitled) (Palíndromo, 2013)
This paper approach the topics Family and Inclusion, discussing aspects of accessibility in the cultural and exhibition spaces. The text presents reflections on the importance of effective programs that integrates people with disabilities, the family and the museum. The dialogue is guided by research conducted in Masters Degree of Visual Arts, completed in 2011, wich explored data about what the families think about the artistic formation of children with disabilities. There is the issue of accessibility in museums and exhibition spaces in Florianópolis, from the speech of the mothers interviewed. It shows possibilities to approximate family of cultural institutions, questing non-formal education field, as well as debates that permeate the cultural heritage and educative mediation.